Kesulitan yang Dihadapi Anak Usia Dini dalam Memahami Teks dan Strategi Mengatasinya - Arifin, Shafira Farha; Wardhani, Wahju Dyah Laksmi; Kusumaningtyas, Nuraini (Jurnal Pendidikan Anak Usia Dini, 2023)
The ability to read is one of the most crucial skills in everyday life. Through reading, a person can acquire knowledge, information, and develop an understanding of the world around them. Good reading skills also form a vital foundation in the learning process at school. This research aims to identify and analyze effective methods for improving early childhood reading abilities, as well as to explore potential challenges faced by young children in understanding text and the factors influencing their reading development. This study is a qualitative case study. The research reveals a significant positive influence of these methods on letter and word recognition, as well as reading comprehension. Therefore, educators and parents can utilize these methods to support and enhance reading abilities, as strong reading skills have long-term benefits for a child's academic development.